Penerapan dan Implementasi Metode Certainty Factor Dalam Sistem Pakar Diagnosa Awal Gangguan Menstruasi PALM-COEIN - Putri Azzahra; Elin Haerani (Forum Kerjasama Pendidikan Tinggi, 2022)
Menstrual disorders are changes that occur in the cycle, the amount of blood, and other changes related to the menstrual cycle. Menstrual disorders are often considered a common problem that can affect daily activities. Menstrual disorders that are ignored on an ongoing basis can cause various reproductive system disorders and are also an early sign of dangerous diseases. Many women ignore the menstrual disorders they experience because they are constrained in consulting a doctor both in terms of time, distance, and cost. To help overcome these obstacles, an expert system can be a solution. This expert system is made using the certainty factor method which consists of 43 symptoms with 7 types of disease. This system produces output in the form of a percentage of the type of possible disease experienced by the user and suggestions based on the symptoms selected by the user. The expert system built is expected to be a medium of information about menstrual disorders and can contribute to providing benefits to the community, especially women, to make an initial diagnosis of menstrual disorders experienced without being constrained in terms of time, distance, or cost